2010
DOI: 10.1111/j.1755-3768.2009.01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of exfoliation syndrome and central retinal vein occlusion: an ultrastructural analysis

Abstract: ABSTRACT.Purpose: To evaluate prospectively the frequency with which exfoliation syndrome (XFS) occurs in patients with central retinal vein occlusion (CRVO) by clinical examination and ultrastructural examination of conjunctival biopsy specimens. Methods: Prospective observational case series. Thirty-six eyes of 36 consecutive patients with CRVO were investigated for XFS by slit-lamp examination and conjunctival biopsy when XFS was not clinically visible on examination. Results: A clinical diagnosis of XFS or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 42 publications
0
40
0
1
Order By: Relevance
“…28,[30][31][32] We have recently investigated the presence of XFS in 36 CRVO eyes using electron microscopy, and a clinical diagnosis or a positive conjunctival biopsy result was found in 22 eyes. 33 We hypothesised that the connection between XFS and RVO might depend on the extent of involvement of an eye by XFS. The findings of this study corroborate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…28,[30][31][32] We have recently investigated the presence of XFS in 36 CRVO eyes using electron microscopy, and a clinical diagnosis or a positive conjunctival biopsy result was found in 22 eyes. 33 We hypothesised that the connection between XFS and RVO might depend on the extent of involvement of an eye by XFS. The findings of this study corroborate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…12 Central retinal vein occlusions occur more commonly in XFS vs controls. 13,14 Systemically, vascular changes include a lower ankle brachial index in XFS vs controls, which suggests an accompanying peripheral vascular disease in XFS. 15 Fingertip cutaneous capillary blood flow measured by laser Doppler flowmetry is lower in XFG compared with POAG and controls and the duration of cold-induced blood flow reduction as well as recovery periods are longer in XFG compared with POAG and controls.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unique nature of NVG, which is known to be a result of CRVO rather than the cause, especially in the ischemic type [3, 9], we analyzed both groups after excluding NVG. We found that RVO was significantly more prevalent in the PXF group ( p = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…The PXF syndrome is known as a major risk factor for the development of glaucoma and is often associated with severe, refractory disease [2, 3, 7]. An association between CRVO and PXF has been shown in some studies, but up to date, it has not yet been proven whether the association between PXF and RVO is by the glaucoma mediator or whether PXF is an independent risk factor for RVO [8, 9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation